Does international talent promote innovation performance of latecomer firms? Empirical investigation into mainland Chinese firms in the Zhangjiang National Innovation Demonstration Zone, Shanghai. Issue 1 (2nd January 2022) - Zhang, Yi; Zeng, Gang; Si, Yuefang; Teng, Tangwei
ABSTRACT: Against the background of 'brain circulation' between developed and developing economies, latecomer firms (LCFs) in Taiwan and India were dedicated to attracting international talent to improve their innovation performance in order to catch up with leading global firms. Inspired by their success, LCFs in mainland China are carrying out a similar internationalisation strategy. However, it is debatable whether international talent can promote their innovation performance due to their business model of 'Technology outside, market inside', which is different from the 'Technology outside, market outside' model of Taiwanese and Indian firms. In this paper, we attempt to identify the relationship between international talent and the innovation performance of mainland Chinese LCFs, as well as other factors influencing their relationship, by studying 4, 685 mainland Chinese enterprises in Zhangjiang National Innovation Demonstration Zone, Shanghai. The results show that there is a curvilinear relationship (U-shaped) between international talent and a firm's innovation performance, and both the internationalisation of R&D and export positively moderate the relationship between international talent and the firm's innovation performance. This paper has important practical implications showing that it is essential to enhance the embeddedness of international talent within firms to promote the innovation capacities of LCFs.